Zero tillage for sustaining land and water productivity in northern India - BHATT, RAJAN; ARORA, SANJAY; BUSARI, M. A. (Journal of Soil and Water Conservation, 2020)
Soil moisture conservation is key priority for improving land and water productivity in all soil textural classes and under every agro-climatic condition. A number of resource conservation technologies are being advocated to uplift water productivity, however, direct drilling of the wheat seeds into the standing rice stubbles comes out to be best as it provides mulch benefits like hindering hot sunrays to strike directly onto the bare soil surface, regulates soil temperature, restricts free diffusion of water vapour, reduces wind speed near to soil surface, reduces cost of cultivation, reduces soil erosion, improving soil health by building organic carbon status and thus finally sustaining long-term crop productivity. In some cases, impacts on grain yield varied and the factors responsible for it need to be identified. The conserved soil moisture helps in reducing the water inputs without affecting the grain yields which further improves the declining water and land productivity however, inspite of these merits significantly higher weed pressure is the single factor which could change the whole story. Thus, benefits of the zero tillage could be realized only after retaining proper mulch loads and with proper control of weeds. In the present review, attempt was made to come out with an effective integrated approach which could be used for successful adoption of the zero tillage in north Indian region.